Right To Die - Stout, Rex (Viking Press, 1964)
When a bright young heiress with a flair for romance and one too many enemies is found brutally murdered, Nero Wolfe and his sidekick, Archie, find themselves embroiled in a case that is not as black and white as it first appears.
66172
Keywords: Traditional Detective Mysteries; Private Investigator Mysteries